THE EFFECT OF DEBT TO EQUITY RATIO, CURRENT RATIO AND INSTITUTIONAL OWNERSHIP ON SHARE RETURNS IN BANKING COMPANIES ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2020 PERIOD - Nurhalimah (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2022)
This study aims to determine the effect of DER, CR, INST on stock returns in banking companies listed on the IDX. This research is a type of quantitative approach. The total population in this study was 46 banking companies, with the research sample used were 4 banking companies. The results of the research that have been obtained conclude that partially DER and CR have a negative and significant effect on stock returns in bank companies. While INST has a positive and significant effect on stock returns in banking companies. And simultaneously DER, CR, and INST have a significant effect on stock returns of banking companies listed on the IDX.